Studi Akumulasi Logam Berat Merkuri Menggunakan Tanaman Awar-Awar (Ficus Septica Burm F) - Mariwy, Abraham; H. Dulanlebit, Yeanchon; Yulianti, Fian (Indonesian Journal of Chemical Research, 2020)
This research aims to to study the ability of awar-awar plants ((Ficus Septica Burm. F)) to accumulate heavy metals. Awar-awar are grown in glass reactors and treated with 10 ppm mercury solution wich one, two, and three weeks in time variations. The analysis using CV-AAS showed that the total absorption of mercury heavy metals by awar-awar plants in reactors I, II and III was 81.7%, 34.6% and 85.4% respectively. When the phytoremediation process takes place the plant shows no symptoms of damage or even death even though it has accumulated more than 50% of mercury from the growing media. The BCF value of awar-awar plants in reactor I was 2.79 reactor II was 0.53 and reactor III was 0.55. While the TF values ​​in reactors I, II and III were 0.04; 1.13 and 0.97. The calculation results of BCF and TF values ​​show that Awar-awar plants (Ficus Septica Burm. F) can accumulate heavy metals of mercury so it is recommended to be used as a phytoremediation agent in mercury-contaminated soils.